2023
DOI: 10.1152/ajpendo.00129.2023
|View full text |Cite
|
Sign up to set email alerts
|

Time-restricted feeding combined with resistance exercise prevents obesity and improves lipid metabolism in the liver of mice fed a high-fat diet

Robson Damasceno de Lima,
Renan Fudoli Lins Vieira,
Vitor Rosetto Muñoz
et al.

Abstract: Non-alcoholic fatty liver disease (NAFLD), a condition characterized by the accumulation of fat in the liver, is estimated to be the most common liver disease worldwide. Obesity is a major risk factor and contributor, and, accordingly, weight loss can improve NAFLD. Previous studies in preclinical models of diet-induced obesity and fatty liver disease have shown the independent benefits of resistance exercise training (RT) and time-restricted feeding (TRF) in preventing weight gain and hepatic build-up of fat.… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

1
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
5

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 108 publications
1
1
0
Order By: Relevance
“…In the present study, 12 weeks of walking, resistance training, and the maintenance of a modest decrease in energy intake promoted significant weight loss (−1.88 [−0.6, −3.2] kg, p = 0.007), fat loss (−2.4 [−1.3, −3.5] kg, p < 0.001), and a reduction in body fat percent (−2.43 [−1.3, −3.5] %, p < 0.001) while increasing FFM (0.54 [0.06, 1.01] kg, p = 0.03) in both treatment groups. These findings are consistent with our prior research [10,36,[72][73][74][75][76][77] and others [78][79][80][81][82][83] that showed that this type of exercise and dietary intervention promotes a reduction in energy intake and fat loss while maintaining or increasing muscle mass and/or REE. However, beyond a trend toward a greater reduction in energy and a significant reduction in fat intake, supplementation with fucoxanthin did not promote a significant increase in REE or greater weight and fat loss compared with those ingesting a placebo.…”
Section: Primary Outcomessupporting
confidence: 93%
“…In the present study, 12 weeks of walking, resistance training, and the maintenance of a modest decrease in energy intake promoted significant weight loss (−1.88 [−0.6, −3.2] kg, p = 0.007), fat loss (−2.4 [−1.3, −3.5] kg, p < 0.001), and a reduction in body fat percent (−2.43 [−1.3, −3.5] %, p < 0.001) while increasing FFM (0.54 [0.06, 1.01] kg, p = 0.03) in both treatment groups. These findings are consistent with our prior research [10,36,[72][73][74][75][76][77] and others [78][79][80][81][82][83] that showed that this type of exercise and dietary intervention promotes a reduction in energy intake and fat loss while maintaining or increasing muscle mass and/or REE. However, beyond a trend toward a greater reduction in energy and a significant reduction in fat intake, supplementation with fucoxanthin did not promote a significant increase in REE or greater weight and fat loss compared with those ingesting a placebo.…”
Section: Primary Outcomessupporting
confidence: 93%
“…TRE significantly reduced FM in this study, potentially because of its impact on circadian rhythms, thereby influencing energy expenditure rates [ 35 , 36 ]. When combined with exercise, TRE has the potential to enhance lipid metabolism, thereby contributing to alterations in glucose and fat consumption rates [ 37 , 38 ]. Although the main increase in lipid metabolism occurs between 18 and 24 h of acute fasting [ 39 ], significant changes can occur during long-term intervention with shorter fasting durations.…”
Section: Discussionmentioning
confidence: 99%